Network attacks and exploitation a framework - Monte, Matthew (John Wiley & Sons, Inc., 2015)
Incorporate offense and defense for a more effective network security strategy Network Attacks and Exploitation provides a clear, comprehensive roadmap for developing a complete offensive and defensive strategy to engage in or thwart hacking and computer espionage